2011
DOI: 10.4103/0974-8520.92579
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Yashtimadhu (Glycyrrhiza glabra) against side effects of radiation/chemotherapy in head and neck malignancies

Abstract: One of the very common side effects of Radiation/Chemotherapy especially of the head and neck malignancies is mucositis. Cancer therapy or the cancer itself may cause changes in the body chemistry that results in loss of appetite, pain, nausea, vomiting, diarrhea and very common mucositis which makes eating difficult. Loss of appetite is followed by an undesirable loss of weight due to insufficient amount of calories every day which can lead to loss of muscle mass and strength and other complications by causin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 0 publications
2
34
0
2
Order By: Relevance
“…5 Herbal drugs offer an alternative to the synthetic compounds and are considered either nontoxic or less toxic than their synthetic counterparts. Natural products with free radical scavenging, antioxidant, antimicrobial, anti-inflammatory, wound healing, radioprotective, and immunostimulatory properties could be of possible use in the prevention of radiation mucositis and previous studies have shown that honey, 2,6 Isatis indigotica, 7 Leptospermum scoparium, 8 Glycyrrhiza glabra, 9 and Kunzea ericoides, 8 possess beneficial effects. The rhizome of Curcuma longa Linn, commonly known as turmeric and belonging to the ginger family, Zingaberaceae is an important spice and a medicinal agent in the various traditional and folk systems of medicine in India, and through different routes of administration, including topically, orally, and by inhalation.…”
Section: Introductionmentioning
confidence: 99%
“…5 Herbal drugs offer an alternative to the synthetic compounds and are considered either nontoxic or less toxic than their synthetic counterparts. Natural products with free radical scavenging, antioxidant, antimicrobial, anti-inflammatory, wound healing, radioprotective, and immunostimulatory properties could be of possible use in the prevention of radiation mucositis and previous studies have shown that honey, 2,6 Isatis indigotica, 7 Leptospermum scoparium, 8 Glycyrrhiza glabra, 9 and Kunzea ericoides, 8 possess beneficial effects. The rhizome of Curcuma longa Linn, commonly known as turmeric and belonging to the ginger family, Zingaberaceae is an important spice and a medicinal agent in the various traditional and folk systems of medicine in India, and through different routes of administration, including topically, orally, and by inhalation.…”
Section: Introductionmentioning
confidence: 99%
“…Complications associated with radiotherapy are often more significant because of the unique oral and maxillofacial anatomy [25]. Schoot et al reported that 70% of patients who undergo radiotherapy for head and neck cancer may experience RTOG complications of grade 3/4 [26].…”
Section: Discussionmentioning
confidence: 99%
“…Even though the QoL score for group B improved mildly 5.66 at 12 months after treatment, treatment effectiveness was far lower than 125 I brachytherapy at 12 months after treatment. Complications associated with radiotherapy are often more significant because of the unique oral and maxillofacial anatomy [25]. Schoot et al reported that 70% of patients who undergo radiotherapy for head and neck cancer may experience RTOG complications of grade 3/4 [26].…”
Section: Osmentioning
confidence: 99%